A Novel Relative High-Density Lipoprotein Index to Predict the Structural Changes in High-Density Lipoprotein and Its Ability to Inhibit Endothelial–Mesenchymal Transition - Lin, Feng-Yen; Lin, Yi-Wen; Shih, Chun-Ming; Lin, Shing-Jong; Tung, Yu-Tang; Li, Chi-Yuan; Chen, Yung-Hsiang; Lin, Cheng-Yen; Tsai, Yi-Ting; Huang, Chun-Yao (International journal of molecular sciences, 2021)
Therapeutic elevation of high-density lipoprotein (HDL) is thought to minimize atherogenesis in subjects with dyslipidemia. However, this is not the case in clinical practice. The function of HDL is not determined by its concentration in the plasma but by its specific structural components. We previously identified an index for the prediction of HDL functionality, relative HDL (rHDL) index, and preliminarily explored that dysfunctional HDL (rHDL index value > 2) failed to rescue the damage to endothelial progenitor cells (EPCs). To confirm the effectiveness of the rHDL index for predicting HDL functions, here we evaluated the effects of HDL from patients with different rHDL index values on the endothelial–mesenchymal transition (EndoMT) of EPCs. We also analyzed the lipid species in HDL with different rHDL index values and investigated the structural differences that affect HDL functions. The results indicate that HDL from healthy adults and subjects with an rHDL index value < 2 protected transforming growth factor (TGF)-β1-stimulated EndoMT by modulating Smad2/3 and Snail activation. HDL from subjects with an rHDL index value > 2 failed to restore the functionality of TGF-β1-treated EPCs. Lipidomic analysis demonstrated that HDL with different rHDL index values may differ in the composition of triglycerides, phosphatidylcholine, and phosphatidylinositol. In conclusion, we confirmed the applicability of the rHDL index value to predict HDL function and found structural differences that may affect the function of HDL, which warrants further in-depth studies.